Good Schools or Good Students? The Importance of Selectivity for School Rankings - Aedín Doris; Donal O'Neill; Olive B. Sweetman (Institute of Labor Economics (IZA), 2019)
This paper uses a rich set of student background characteristics, including early measures of cognitive and non-cognitive skills, to estimate the value added of second-level schools in Ireland. Although there are high performing schools in both raw and value-added terms, there is a considerable degree of reranking of schools when we move to value added. In many cases the best performing schools in raw terms are not the best in value-added terms. In addition we find that parents tend to choose schools on the basis of raw results rather than value added. We estimate that if parents chose the best value-added school from among the set of feasible schools, then this reallocation of students would increase academic achievement substantially.
Keywords: I21; I28; 330; school value added; school choice